Practical Significance of Studying Diffusion Processes in Semiconductors (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article shows the practical relevance of studying diffusion processes in semiconductors, which has educational and scientific-practical significance for the creation of semiconductor devices with specified properties and their production technologies.